A bidirectional virtual teaching platform for postgraduate Point-of-Care Ultrasound training: A proof-of-concept study - Ralhan, Aanchal; Jacques, Queen; MacDonald, Alison; Sheppard, Gillian; Rogers, Peter; Stone-McLean, Jordan (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2026)
Implication StatementPoint-of-Care Ultrasound (POCUS) has become an important modality for procedural guidance and patient diagnostics. However, rural postgraduate trainees in Canada who need to acquire these knowledge and skills face barriers to accessing POCUS training, in part because of a lack of qualified onsite teaching faculty. To help address this issue, our study describes a novel, relatively easy to implement, approach to teach POCUS to postgraduate trainees who do not access to the resources at larger, more well-funded sites. This allows experienced POCUS instructors to teach remotely, which would improve access to POCUS training for both medical learners in remote sites and continuing professional development for rural physicians. Additionally, it offers a cost-effective solution that reduces travel-related expenses for both trainees and faculty. It also provides a unique approach to remote medical education and ongoing skill development.